THE RELATIONSHIP BETWEEN PLACE OF RESIDENCE AND OCCUPATION WITH ISCHEMIC HEART DISEASE (IHD) - K.Holakui Naini; R. miri; Z. Hatmi (Tehran University of Medical Sciences, 1998)
IHD as a modern epidemic of our age is one of the main causes of mortality in Iran. This research was done in order to determine the relationship between place of residence and place of occupation (as indicator of air pollution exposures) and other risk factors with IHD. This is a case- control study of IHD involving 191 men aged 45 -70 years. The cases were 91 male patients with myocardial infarction hospitalized at Bu Ali hospital, and their diagnosis confirmed with enzymatic and electrocardiography. Controls were 100 male patients without myocardial infarction being attended at other wards of Bu Ali hospital. Data on set of risk factors, age, place of residence, place of occupation, cigarette smoking, hypercholestrolemia. Diabetes mellitus and hypertension were obtained from case and controls by questionnaire and physical examination and laboratory tests. Results indicated that hypertension (P